Language, Ethno-nationalism and the South African university - Lloyd Hill (Modern Africa, 2019)
This article presents a conceptual analysis of the relations between language, ethnicity, and nationalism – within the domain of the university. While an analytical distinction is commonly madbetween “ethnicity” and “nationalism,” here “ethno-nationalism” is used to highlight aspects of cultural continuity between these constructs and to draw attention to problematic “telementational” assumptions about the vehicular role of “languages” in influential modernist theories of nationalism (notably Ernest Gellner and Benedict Anderson). The empirical focus of the article falls on long-run institutional changes in the South African university system; and on the deployment of ideas about ethnicity, nationalism, language, and race. While assumptions about the vehicular capacity of languages have deep roots in the colonial and apartheid periods, these also feature prominently in post-apartheid debates on the transformation of the university system.